Increasing irrigation benefits and sustainability by integrating fisheries. - Food and Agriculture Organization of the United Nations; WorldFish; International Water Management Institute (2019)
Water managers shouldn’t be resistant to integrating fisheries into irrigation systems. Rather, it’s an opportunity to sustain the benefits of irrigation projects and, at the same time, increase fish production and reduce conflict between water users.